Biobanking in everyday clinical practice in psychiatry—The Munich Mental Health Biobank - Kalman, Janos L.; Burkhardt, Gerrit; Adorjan, Kristina; Barton, Barbara B.; De Jonge, Sylvia; Eser-Valeri, Daniela; Falter-Wagner, Christine M.; Heilbronner, Urs; Jobst, Andrea; Keeser, Daniel; Koenig, Christian; Koller, Gabi; et al. (Frontiers in Psychiatry, 2022)
Translational research on complex, multifactorial mental health disorders, such as bipolar disorder, major depressive disorder, schizophrenia, and substance use disorders requires databases with large-scale, harmonized, and integrated real-world and research data. The Munich Mental Health Biobank (MMHB) is a mental health-specific biobank that was established in 2019 to collect, store, connect, and supply such high-quality phenotypic data and biospecimens from patients and study participants, including healthy controls, recruited at the Department of Psychiatry and Psychotherapy and the Institute of Psychiatric Phenomics and Genomics, University Hospital of the Ludwig-Maximilians-University (LMU), Munich, Germany. Participants are asked to complete a questionnaire that assesses sociodemographic and cross-diagnostic clinical information, provide blood samples, and grant access to their existing medical records. The generated data and biosamples are available to both academic and industry researchers. In the current manuscript, we outline the workflow and infrastructure of the MMHB, describe the clinical characteristics and representativeness of the sample collected so far, and reveal future plans for expansion and application. As of October 31, 2021 the MMHB contains a continuously growing set of data from 578 patients and 104 healthy controls (46.37% female; median age, 38.31 years). The five most common mental health diagnoses in the MMHB are recurrent depressive disorder (38.78%; ICD-10: F33), alcohol-related disorders (19.88%; ICD-10: F10), schizophrenia (19.69%; ICD-10: F20), depressive episode (15.94%; ICD-10: F32), and personality disorders (13.78%; ICD-10: F60). Compared with the average patient treated at the recruiting hospitals, MMHB participants have significantly more mental health-related contacts, less severe symptoms, and a higher level of functioning. The distribution of diagnoses is also markedly different in MMHB participants compared with individuals who did not participate in the biobank. After establishing the necessary infrastructure and initiating recruitment, the major tasks for the next phase of the MMHB project are to improve the pace of participant enrollment, diversify the sociodemographic and diagnostic characteristics of the sample, and improve the utilization of real-world data generated in routine clinical practice.